Pangolo Sompa in Bugis Marriage in Bone Regency from the Perspective of Al-‘Adah Muhakkamah - Henrawan, Henrawan (USRATY : Journal of Islamic Family Law, 2025)
The main problem addressed in this study lies in the contradiction between the enduring cultural practice of pangolo sompa in Bugis marriage traditions and the growing perception that it may conflict with Islamic law in the modern era. This research aims to analyze the existence and transformation of pangolo sompa in Bugis marriage customs in Bone Regency and to examine its implementation from the perspective of al-‘adah muhakkamah in Islamic law. This study is a field research employing a qualitative approach. The data sources consist of community leaders, religious figures, and married couples in Bone Regency. Data were collected through observation, in-depth interviews, and documentation, and analyzed using descriptive qualitative methods through the stages of data reduction, data presentation, and conclusion drawing. The findings reveal that pangolo sompa remains significant as a symbol of honor, responsibility, and kinship, although its meaning has shifted due to modernization and changing religious interpretations. The novelty of this study lies in demonstrating that pangolo sompa, when viewed through al-‘adah muhakkamah, aligns with Islamic legal principles as long as it avoids discrimination and excessive burden. The study contributes academically by strengthening the global discourse on the integration of local wisdom and Islamic jurisprudence, highlighting how local customs can coexist harmoniously with religious law in various Muslim societies and offering a model for understanding cultural adaptation within Islamic legal frameworks.